2022
DOI: 10.7759/cureus.25349
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy and Safety of Early Intracoronary Nicorandil Administration in Patients With ST-Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Background No-reflow phenomenon (NRP) remains a challenge in ST-elevation myocardial infarction (STEMI) patients. We determined the efficacy and safety of early intracoronary administration of nicorandil as an adjunct to primary percutaneous coronary intervention (pPCI) in STEMI patients to reduce the risk of NRP. Materials and methods In this single-center case-control prospective study, 100 STEMI patients who underwent pPCI had thrombectomy performed using a suction catheter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Nicorandil abolished homocysteine‐induced coronary MVO in mice [163]. It was reported that nicorandil reduced the incidence of MVO in patients with AMI and PCI [164–168].…”
Section: Katp Channels Collateral Blood Flow No‐reflow Phenomenon And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nicorandil abolished homocysteine‐induced coronary MVO in mice [163]. It was reported that nicorandil reduced the incidence of MVO in patients with AMI and PCI [164–168].…”
Section: Katp Channels Collateral Blood Flow No‐reflow Phenomenon And...mentioning
confidence: 99%
“…It was reported that nicorandil reduced the incidence of MACE in patients with AMI and PCI [165, 176]. It was found that the nicorandil prevents the development of heart failure and improves cardiac function after PCI in patients with AMI [167, 168]. Treatment with nicorandil decreased infarct size detected by cardiac magnetic resonance imaging in patients with AMI and PCI [168].…”
Section: The Use Of Nicorandil In Treatment Of Patients With Ami or C...mentioning
confidence: 99%
“…For the evaluation of regional and global left ventricular systolic function (LVSF), the two-dimensional transthoracic echocardiography (TTE) is used 8 . LVEF is an autonomous predictive aspect that is considered to be the condition commonly associated with LVSF 9 . For the estimation, the LVEF Simpson method is considered to be effective, and in addition, a skillful echocardiographer is mandatory for observation of the border of the endocardial line.…”
Section: Introductionmentioning
confidence: 99%